PEMBERIAN PENGETAHUAN MENGENAI EKONOMI POLITIK KEPADA REKAN-REKAN ALUMNI - Posma Sariguna Johnson Kennedy (National Conference for Community Service Project (NaCosPro), 2020)
In this era of information disclosure, the campaign to win a candidate is carried out in various ways. The purpose of this Community Service is to conduct socialization so that recipients of information will not be trapped in a heated situation with lots of hoaxes and misleading information. This activity was carried out using the focus group discussion method through the online "WhatsUp group" and fellow alumni from the Department of Civil Engineering, Institute of Technology Bandung '92. The output target is to provide socialization and increase understanding of all information circulating in the presidential election campaign period from a political economy perspective. Participants felt enlightened and began to understand the situation in society ahead of the Presidential election.